Rethinking a Negative Event: The Affective Impact of Ruminative versus Imagery-Based Processing of Aversive Autobiographical Memories - Slofstra, Christien; Eisma, Maarten C.; Holmes, Emily A.; Bockting, Claudi L. H.; Nauta, Maaike H. (Frontiers in Psychiatry, 2017)
Ruminative (abstract verbal) processing during recall of aversive autobiographical memories may serve to dampen its short-term affective impact. Experimental studies indeed demonstrate that verbal processing of non-autobiographical material and positive autobiographical memories evokes weaker affective responses than imagery-based processing. In the current study, we hypothesized that abstract verbal or concrete verbal processing of an aversive autobiographical memory would result in weaker affective responses than imagery-based processing. The affective impact of abstract verbal versus concrete verbal versus imagery-based processing during recall of an aversive autobiographical memory was investigated in a non-clinical sample (N = 99) using both an observational and an experimental design. Observationally, it was examined whether spontaneous use of processing modes (both state and trait measures) was associated with impact of aversive autobiographical memory recall on negative and positive affect. Experimentally, the causal relation between processing modes and affective impact was investigated by manipulating the processing mode during retrieval of the same aversive autobiographical memory. Main findings were that higher levels of trait (but not state) measures of both ruminative and imagery-based processing and depressive symptomatology were positively correlated with higher levels of negative affective reactivity in the observational part of the study. In the experimental part, no main effect of processing modes on affective impact of autobiographical memories was found. However, a significant moderating effect of depressive symptomatology was found. Only for individuals with lower levels of depressive symptomatology, concrete verbal (but not abstract verbal) processing of the aversive autobiographical memory did result in weaker affective responses, compared to imagery-based processing. These results cast doubt on the hypothesis that ruminative processing of aversive autobiographical memories serves to avoid the negative emotions evoked by such memories. Furthermore, findings suggest that depressive symptomatology is associated with the spontaneous use and the affective impact of processing modes during recall of aversive autobiographical memories. Clinical studies are needed that examine the role of processing modes during aversive autobiographical memory recall in depression, including the potential effectiveness of targeting processing modes in therapy.